2019
DOI: 10.1007/s10270-019-00757-6
|View full text |Cite
|
Sign up to set email alerts
|

Modeling languages in Industry 4.0: an extended systematic mapping study

Abstract: Industry 4.0 integrates Cyber-Physical Systems with the Internet of Things to optimize the complete value-added chain. Successfully applying Industry 4.0 requires the cooperation of various stakeholders from different domains. Domain-specific modeling languages promise to facilitate their involvement through leveraging (domain-specific) models to primary development artifacts. Objective: We aim to assess the use of modeling in Industry 4.0 through the lens of modeling languages in a broad sense. Method: Based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(55 citation statements)
references
References 134 publications
0
48
0
2
Order By: Relevance
“…Concerning methods used in dealing with RE process, it is not surprising that object-oriented becomes the most popular approach (see Fig. 4) used in each software development project, due to the popularity of the Unified Modeling Language (UML) and object technology [11] [12] [13] [14]. Further, most of the respondents reported that group interviews and rapid prototyping are the most two techniques used in performing requirements elicitation.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning methods used in dealing with RE process, it is not surprising that object-oriented becomes the most popular approach (see Fig. 4) used in each software development project, due to the popularity of the Unified Modeling Language (UML) and object technology [11] [12] [13] [14]. Further, most of the respondents reported that group interviews and rapid prototyping are the most two techniques used in performing requirements elicitation.…”
Section: Discussionmentioning
confidence: 99%
“…Model-driven development (MDD) can decrease manual implementation efforts significantly [ 13 ]. However, as Wortmann et al [ 14 ] point out, there is a lack of adequate metrics and quantitative evaluations in the domain of MDD for I4.0.…”
Section: Integration Of Systems and Accessibility Of Data As Prerementioning
confidence: 99%
“…Already today, industry 4.0 integrates people and digitally controlled machines with the Internet and information technologies [2]. On the one hand, the information flow is carried out at the level of production process between the machines, on the other hand, the process information obtained supports company management systems, which makes it easier to forecast production efficiency.…”
Section: Introductionmentioning
confidence: 99%